Surveillance, Islamophobia, and Sikh Bodies in the War on Terror. Issue 1 (1st October 2017) - Katy P. Sian
Abstract : In the aftermath of 9/11, there has been a wave of intensified surveillance throughout Western democracies in the moral panic surrounding national security. This article will explore the way in which Sikh bodies have become problematized against the backdrop of harsher profiling and policing measures directed at racialized populations. Based upon empirical data, including a series of semi-structured interviews with Sikh respondents carried out in Canada and the US, the article will examine the experiences of Sikhs post-9/11 through critical race and postcolonial conceptual frameworks, as a way to understand the processes by which they have been governed and regulated in the landscape of an obsessive monitoring of 'suspicious' brown bodies.